LIMITING PRESSURE ON A CRICULAR PILE LOADED LATERALLY IN COHESIVE SOIL. - Randolph, M; Houlsby, G (1984)
In the analysis of the undrained loading of laterally loaded piles an important quantity is the ultimate lateral resistance at depth to purely horizontal movement. If the soil is modeled as a perfectly plastic cohesive material then the calculation of this quantity reduces to a plane strain problem in plasticity theory, in which the load is calculated on a long cylinder which moves laterally through an infinite medium. An exact calculation of the load on such a cylinder is presented. If this load is non-dimensionalized with respect to the soil strength and the diameter of the pile, it is found that the load factor varies between 6 plus 72 for a perfectly smooth pile and 4 ROOT 2 plus 2 eta for a perfectly rough pile. Refs.